PENGEMBANGAN MODEL PEMBELAJARAN PEMERANAN BERORIENTASI TEKNIK CS PADA TEATER TRADISI - alfirdaus, moh mujib (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2018)
This learning model is the author's attempt to develop acting method in traditional theater through the Stanislavski's technique, although the need for theater tradition performances and theater conventional realism performance is different. During this time the method of play in the theater tradition is still spontaneous, but the method of acting on the theater tradition must be measurable and can be studied in the academic field, hence, the author develops acting methods based on Stanislavski's technique as a reference in learning. An actor is a student for nature and pupil for anyone as long as the knowledge he earned is useful to develops his acting creativity. Therefore this Stanislavski's method becomes very influential to train the actor's intelligence, despite his need for traditional theater. Why is Stanislavski's method becoming important to be learned by actor candidate ?. Because the analysis used by Stanislavski's method is still very logical and reasonable, it did not rule out the effects of int elligence for anyone who applied it. This circumstance emphasizing the importance of Developing Stanilavski's technique-oriented Learning Model on Traditional Theater. In order for candidates who will perform for traditional and modern show, are expected to be ready with all the acting devices to employ. Therefore, this learning method need to be applied, especially in STKW Surabaya. The purpose of this research is developing a learning model for acting in the theater tradition. This research carried out by producing several outcome. First, a handbook of Stanislavski's method learning model for student. Second, a lecturer's handbook for an effective and efficient learning process